Molecular Genetic and Functional Characterization Implicate Muscle-Restricted Coiled-Coil Gene (MURC) as a Causal Gene for Familial Dilated Cardiomyopathy - Rodriguez, Gabriela; Ueyama, Tomomi; Ogata, Takehiro; Czernuszewicz, Grazyna; Tan, Yanli; Dorn, Gerald W.; Bogaev, Roberta; Amano, Katsuya; Oh, Hidemasa; Matsubara, Hiroaki; Willerson, James T.; Marian, Ali J. (Circulation. Cardiovascular genetics, 2011)
BACKGROUND—Dilated cardiomyopathy (DCM) and hypertrophic cardiomyopathy (HCM) are classic forms of systolic and diastolic heart failure, respectively. Mutations in genes encoding sarcomere and cytoskeletal proteins are major causes of HCM and DCM. MURC, encoding muscle-restricted coiled-coil, a Z-line protein, regulates cardiac function in mice. We investigated potential causal role of MURC in human cardiomyopathies. METHODS AND RESULTS—We sequenced MURC in 1199 individuals, including 383 probands with DCM, 307 with HCM, and 509 healthy control subjects. We found 6 heterozygous DCM-specific missense variants (p.N128K, p.R140W, p.L153P, p.S307T, p.P324L, and p.S364L) in 8 unrelated probands. Variants p.N128K and p.S307T segregated with inheritance of DCM in small families (χ=8.5, P=0.003). Variants p.N128K, p.R140W, p.L153P, and p.S364L were considered probably or possibly damaging. Variant p.P324L recurred in 3 independent probands, including 1 proband with a TPM1 mutation (p.M245T). A deletion variant (p.L232-R238del) was present in 3 unrelated HCM probands, but it did not segregate with HCM in a family who also had a MYH7 mutation (p.L907V). The phenotype in mutation carriers was notable for progressive heart failure leading to heart transplantation in 4 patients, conduction defects, and atrial arrhythmias. Expression of mutant MURC proteins in neonatal rat cardiac myocytes transduced with recombinant adenoviruses was associated with reduced RhoA activity, lower mRNA levels of hypertrophic markers and smaller myocyte size as compared with wild-type MURC. CONCLUSIONS—MURC mutations impart loss-of-function effects on MURC functions and probably are causal variants in human DCM. The causal role of a deletion mutation in HCM is uncertain.